Expeditious Synthesis of the Hexasaccharide Repeating Unit of the Capsular Polysaccharide of Streptococcus pneumoniae Type 7A - Jana, Swapan Kumar; Sahaji, Samim; Shit, Pradip; Misra, Anup Kumar (Synthesis, 2023)
The hexasaccharide repeating unit corresponding to the capsular polysaccharide of Streptococcus pneumoniae type 7A has been synthesized in good yield using [3+2+1] block synthetic strategy. The synthetic strategy involved a number of challenging stereoselective glycosylation steps, which include β-selective glycosylation of l-rhamnosyl thioglycoside donor, α-selective glycosylations of 2-azido-2-deoxy-d-glucopyranosyl thioglycoside donor and d-galactopyranosyl donor together with the formation of β-glycoside of d-galactosamine moiety and α-glycoside of l-rhamnosyl moiety. Suitably functionalized thioglycosides have been used as glycosyl donors and a combination of N-iodosuccinimide (NIS) and trimethylsilyl trifluoromethanesulfonate (TMSOTf) has been used as glycosylation promoter.
Keywords: carbohydrates; glycosylation; glycoside; oligosaccharide; synthesis; Streptococcus pneumoniae